Ethnography #9 - Klima, Alan, 1964- (Book collections on Project MUSE., 2019)
"ETHNOGRAPHY #9 looks at Thai spiritual and financial practices, and at the relationship of these local practices to global capitalism's abstraction of monetary value. Through his examination of moneylending, gambling, funeral casinos, and the consultation of spirits and mediums to predict winning lottery numbers, Alan Klima challenges the assumptions of anthropology's "ontological turn" and reveals the limitations of theoretical explanations of capitalist fantasy that are grounded in the rational and the "real." Looking critically at the work done by conventional ethnographic writing in performing the very objectivity and realism that it claims as its method, Klima instead embraces a distinctive literary form of storytelling that hovers between being and not being, presence and absence, fiction and non-fiction, and fantasy and reality"--